Employment Mobility of FDI Workers in Vietnam: New Evidence from Recent Surveys - Cuong Viet Nguyen (Global Labor Organization (GLO), 2021)
In this study, we examine characteristics of employment in FDI in Vietnam. Workers from FDI account for 5.6% of working people. Female and younger people are more likely to work the FDI sector. Compared with private and public sectors, the FDI sector has a lower share of workers who have tertiary education. The FDI sector has a high proportion of workers with social insurance, at 95%. However, there is a relatively large proportion of the FDI workers receiving daily wages and piece payment. The FDI workers have a high number of working hours and more likely to have overtime working hours. The FDI workers have lower wages per hour than those in the private and public sector. However, once observed characteristics of workers are controlled for, the FDI workers have higher hourly and monthly wages than the private as well as public workers. The proportion of FDI workers who moved out of the FDI sector was 11% over a three-month period and 31% over a two-year period. Older workers are more likely to move out of the FDI sector than young ones. There is no evidence that workers move out of the FDI sector after age 35.
Keywords: 330; FDI; employment; labor; Vietnam